2011
DOI: 10.4061/2011/152125
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Advanced Non-Small-Cell Lung Cancer Patients: Patient Characteristics and Type of Chemotherapy

Abstract: Eleven prognostic factors were retrospectively analyzed in 270 newly diagnosed patients with advanced non-small-cell lung cancer including age, sex, performance status, histology, stage, smoking status, hemoglobin level, forced expiratory volume in one second (FEV1), weight loss >5% in 3 months preceding therapy, number of involved organs, and type of first-line chemotherapy. Response rate was 35.6%, and median survival was 8.2 months (95% CI, 7.8 to 8.7) for the whole group. Age ≤60 years (P = .016), FEV1 ≥ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 13 publications
0
35
0
Order By: Relevance
“…It's higher than that observed in overall Iraq, GCC countries, USA and Australia. The proportion of Large cell: *Computed by the authors; Data from (AlMadouj et al, 2011); ** Computed by the authors; Data from (Abbasi and Badheeb, 2010) Carcinoma (11.61%), lower than that observed in Egypt and Australia, higher than that observed in overall Iraq, GCC countries, Jordan and UAS. The proportion of adenocarcinoma (6.79%), lower than proportion of overall Iraq, and several Arab and developed countries such as, GCC countries, Egypt, Jordan, Australia and USA.…”
Section: Discussionmentioning
confidence: 97%
“…It's higher than that observed in overall Iraq, GCC countries, USA and Australia. The proportion of Large cell: *Computed by the authors; Data from (AlMadouj et al, 2011); ** Computed by the authors; Data from (Abbasi and Badheeb, 2010) Carcinoma (11.61%), lower than that observed in Egypt and Australia, higher than that observed in overall Iraq, GCC countries, Jordan and UAS. The proportion of adenocarcinoma (6.79%), lower than proportion of overall Iraq, and several Arab and developed countries such as, GCC countries, Egypt, Jordan, Australia and USA.…”
Section: Discussionmentioning
confidence: 97%
“…Also, consistent with prior studies, female sex (P = .05; OR, 0.41) predicted improved outcomes. 3,16,17 We performed a matched cohort comparison of these patients to a subset of stage IV patients who received chemotherapy alone and identified the patients who received definitive thoracic radiation therapy as having improved local control and overall survival compared with patients who did not. However, there are several weaknesses to such an analysis, including selection bias and the potential impact of confounders.…”
Section: Discussionmentioning
confidence: 99%
“…3,10,11 In previous studies, it has been clearly demonstrated that MPV is associated with systemic inflammation as well as thromboembolism. 3,10,11 In previous studies, it has been clearly demonstrated that MPV is associated with systemic inflammation as well as thromboembolism.…”
Section: Discussionmentioning
confidence: 99%
“…Many prognostic factors have been determined to estimate for clinical course in patients with NSCLC but majority of the defined prognostic factors in NSCLC have been not used in clinical practice yet. 3,10,11 In previous studies, it has been clearly demonstrated that MPV is associated with systemic inflammation as well as thromboembolism. 6,8,10 Some studies have reported a relationship between increased MPV in cardiovascular and cerebrovascular diseases, in which systemic inflammation has an effect on disease prognosis and severity.…”
Section: Discussionmentioning
confidence: 99%